2008
DOI: 10.1158/0008-5472.can-07-5311
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MAPK Kinase Signaling Pathways Suppressed Renal Cell Carcinoma Growth and Angiogenesis In vivo

Abstract: The mitogen-activated protein kinase (MAPK) signaling pathways play essential roles in cell proliferation and differentiation. Recent studies also show the activation of MAPK signaling pathways in tumorigenesis, metastasis, and angiogenesis of multiple human malignancies, including renal cell carcinoma (RCC). To assess the role of this pathway in regulating the proliferation and survival of RCC cells, we first examined the expression of MAPK kinase (MKK) and MAPK in clear cell RCC and confirmed the overexpress… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
145
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(153 citation statements)
references
References 44 publications
8
145
0
Order By: Relevance
“…Our group and other investigators have reported the critical role played by the oncogenic PI3K/Akt, NF-kB and MAPK signaling pathways as well as by the developmental Notch and SHH-Gli signaling in human CCC tumorigenesis (Sourbier et al, 2006Huang et al, 2008;Sjolund et al, 2008;Dormoy et al, 2009). In all cases, these pathways were shown to be constitutively activated and turned towards tumor growth regardless of VHL status.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Our group and other investigators have reported the critical role played by the oncogenic PI3K/Akt, NF-kB and MAPK signaling pathways as well as by the developmental Notch and SHH-Gli signaling in human CCC tumorigenesis (Sourbier et al, 2006Huang et al, 2008;Sjolund et al, 2008;Dormoy et al, 2009). In all cases, these pathways were shown to be constitutively activated and turned towards tumor growth regardless of VHL status.…”
Section: Discussionmentioning
confidence: 68%
“…The PI3K/Akt, NF-kB, MAPK, Notch and SHH signaling pathways are activated constitutively in human CCC (Sourbier et al, 2006Huang et al, 2008;Sjolund et al, 2008;Dormoy et al, 2009) strongly suggesting that tumor cells reactivate developmental pathways for their growth, invasion and immune escape. Here, we show that Lim1 regulates the activation of the oncogenic pathways PI3K/Akt, NF-kB and MAPK; and also regulates the expression and/or activity of a broad range of oncogenic pathways and molecular factors involved in cell apoptosis, proliferation and movements, and in angiogenesis processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the MAPK signaling pathway has a significant role in the regulation of a number of cellular processes, including cell growth and proliferation, differentiation, and apoptosis (16). Therefore, the present study investigated whether eupatilin was able to induce the activation of MAPK cascades in 786-O cells.…”
Section: Eupatilin Activates Erk Jnk and P38 In 786-o Cellsmentioning
confidence: 95%
“…Recent studies have shown the activation of MAPK signaling pathways including extracellular signal-regulated protein kinase (ERK), c-Jun amino-terminal kinases (JNK), and p38 MAPK (p38) in tumorigenesis, metastasis, and angiogenesis of multiple human malignancies (Huang et al, 2008).…”
Section: Barbigerone Inhibits Tumor Angiogenesis Growth and Metastasmentioning
confidence: 99%